Algunos vocablos del léxico capilar en el español de México : Octavio Cano Silva, Ioana Alexandrescu - Cano Silva, Octavio; Alexandrescu, Ioana (Acta Hispanica, 2014)
Our paper deals with some words belonging to the hair-related vocabulary in Mexican Spanish. It aims to track these words in five recent dictionaries of Spanish, in order to achieve a panoramic view on two issues: their coverage and the way they are dealt with in these dictionaries. The five dictionaries compared are the following: Diccionario del español de México, Diccionario de la lengua española by the Real Academia Española, Diccionario escolar, Diccionario de mexicanismos y Diccionario académico de americanismos. The methodological contribution of our paper lies on the fact that it puts on the same level these dictionaries, while the point of comparison usually is the Real Academia Española’s dictionary, and its cultural one is given by the attempt to retrieve words that are very common and widely used in Mexican Spanish but lack lexicographical registration.